Kyoto Protocol and emission trading: Does the US make a difference? - Umberto Ciorba; Alessandro Lanza; Francesco Pauli (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper presents an estimate of the costs of reducing CO2 emissions asagreed in Kyoto by Annex 1 countries. Unlike most of the existing literature, this paper uses an Almost Ideal Demand System model for energyproducts to estimate the role of each country within the Annex 1 market. A major result is the provision of marginal (and total) abatement costs foreach. The recent position of the US is also discussed, showing the cost ofsome alternative outcomes.
Keywords: C13; C21; C53; Q38; Q41; Q48; 330; Environmental policy; Kyoto protocol; international agreements; CO2 emission; emission trading; marginal abatement cost; Umweltabkommen; Klimaschutz; Emissionshandel; Nachfragesystem; Industriestaaten